Global governance and the emergence of global institutions for the 21st century / Augusto Lopez-Claros, Arthur Lyon Dahl, Maja Groff. - Lopez-Claros, Augusto; Dahl, Arthur L.; Groff, Maja (Cambridge University Press, 2020)
Is there any hope for those who despair at the state of the world and the powerlessness of governments to find a way forward? Global Governance and the Emergence of Global Institutions for the 21st Century provides ambitious but reasonable proposals to give our globalized world the institutions of international governance necessary to address effectively the catastrophic risks facing humanity that are beyond national control. The solution, the authors suggest, is to extend to the international level the same principles of sensible governance that exist in well-governed national systems: rule of law, legislation in the common interest, an executive branch to implement such legislation, and courts to enforce it. The best protection is unified collective action, based on shared values and respect for diversity, to implement widely accepted international principles to advance universal human prosperity and well-being. This title is also available as Open Access.